2011
DOI: 10.1016/j.jada.2010.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of a Low-Fat Diet in the Prevention of Breast and Ovarian Cancer

Abstract: Background Results of the Women’s Health Initiative Randomized Controlled Dietary Modification Trial (WHI-DM) suggest that a low-fat diet may be associated with beneficial health outcomes for specific groups of women. Objective The objective is to assess how cost-effective the WHI-DM would be if implemented as a public health intervention and under the sponsorship of private health insurers and Medicare. Breast and ovarian cancers are the health outcomes of interest. Participants Two groups of WHI-DM parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Table 1 presents the quality of the six studies included, ranging from 74 to 89%. Bós et al ranked the highest score for very good quality, followed by Frew et al and Peels et al (37,39,40), while the lowest score was found for Annemans et al (36). All studies underperformed in category 2 ("data collection").…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 97%
See 3 more Smart Citations
“…Table 1 presents the quality of the six studies included, ranging from 74 to 89%. Bós et al ranked the highest score for very good quality, followed by Frew et al and Peels et al (37,39,40), while the lowest score was found for Annemans et al (36). All studies underperformed in category 2 ("data collection").…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 97%
“…The median cost-effectiveness (in 2018 USD) reported in the four studies, of which ICER/QALY was estimated and for which the price-year was available, was $24,973 (37,(39)(40)(41). From a societal perspective, 80% of the interventions had a ratio below $50,000 WTP threshold (as shown in Table 2).…”
Section: Cost-effectiveness Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to a lack of randomized controlled trials (RCTs) in humans, adequate reporting of safety in publications of randomized controlled trials is a pre-requisite for accurate and comprehensive profile evaluation of conventional as well as complementary and alternative medicine (CAM) treatments. An evaluation of safety reporting in the reports of CAM RCTs across 15 different CAM interventions demonstrated that the reporting of harms was largely inadequate 46 . The reasons for inadequate reporting are currently unclear.…”
Section: Discussionmentioning
confidence: 99%